Efektivitas Nudge dalam Pemasaran Produk Minuman Jamu di PT. Bhineka Rahsa Nuantara - Zaky, Raihana Nanditha; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Indonesia's wealth in the agricultural sector has resulted in many processed agricultural products, one of which is Jamu. Jamu is the health drink of choice because it is known for its more natural and safe benefits, especially during the Covid-19 pandemic. This condition opens up opportunities for Jamu to improve various sectors in Indonesia, especially in trade sector. Many companies use Jamu as their business process, one of which is Rahsa Nusantara. However, in marketing activities, sales are still relatively fluctuating and still rely on paid advertising, so more appropriate strategies are needed, such a nudge. There are several factors other than environmental aspects that can influence effectiveness nudge in selecting health products. For example, a person's behavior such as impulsivity, price sensitivity, decision-making style, and food choice motives. Therefore, this research explores the relationship between income and strategy nudge as well as shopping frequency with strategy nudge. Primary data was obtained from distributing questionnaires with a sample size of 92 obtained from the Slovin formula. The research results were then analyzed using descriptive statistical analysis methods and cross tabulation analysis. From this research, it was found that there is a relationship between shopping frequency and strategy nudge as well as income with strategy nudge.